Pengembangan Usaha Kelompok Pengolah Amplang Ikan Bandeng (Chanos Chanos) Mekar Jaya Di Kelurahan Sungai Parit Kabupaten Penajam Paser Utara - Aqsha, Farizky; Gunawan, Bambang Indratno; Sugiharto, Eko (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2024)
This research aims to describe the problems and examine the development of the Mekar Jaya Milkfish Amplang Processing Group in Sungai Parit Village, North Penajam Paser Regency. This research was carried out from October 2022 to December 2023 in Sungai Parit Village. The sample consisted of 7 respondents using saturated sampling (census) and purposive sampling methods. Data analysis uses descriptive analysis methods and the theory of business development stages (Anoraga, 2007). The results of the research show that the problems faced by the Mekar Jaya Milkfish Amplang Processing Group consist of a lack of availability of milkfish raw materials, a lack of labor and increasing prices of raw materials such as oil and others. The development study takes the form of development stages (Anoraga, 2007) which include, Stage I to Stage III which explains the identification of business opportunities, business formulation to the selection of the milkfish amplang business as the main business and Stages IV to Stage V explain the implementation of the business to the evaluation of the amplang business milkfish. The role of BAZNAS and the Fisheries Service as stakeholders is to carry out business development for the Mekar Jaya Milkfish Amplang Processing Group which is divided into 4 development aspects, namely business capital, product production, product promotion and facilities and infrastructure.